Modified graphene sheet stacks for hydrogen binding - Lesnicenoks, Peteris; Zemitis, Janis; Grinberga, Liga; Chikvaidze, George; Kleperis, Janis; Urbonavičius, Marius; Tačkute, Simona; Milčius, Darius (Kauno Technologijos Universitetas, 2017)
Graphene sheet stacks were obtained using electrochemical exfoliation method. The morphology, distribution of elements and structure of the obtained samples were investigated using scanning electron microscopy, energy dispersive spectroscopy, Raman spectroscopy and Brunauer-Emmett-Teller methods. The graphene sheet stacks mostly have been formed with open stack structures having surface area of 124 m2/g. Mg intercalation in graphene sheet structures was obtained adding MgCl2 during exfoliation process. Hydrogen desorption were measured in the temperature range 100 – 473 K at the pressure 2 bar reaching maximal desorbed hydrogen amount of 0.12 – 0.43 wt.%.
Results are partially obtained using infrastructure of Lithuanian Energy Institute with support of COST Action MP1103 “Nanostructured materials for solid-state hydrogen storage”. Latvian National Research program IMIS2 is greatly acknowledged for financial support
Keywords: hydrogen storage; graphene; exfoliation; multi-sheet stacks; Research Subject Categories::NATURAL SCIENCES:Physics